Follicular Unit Extraction (FUE) Hair Transplantation in Combination with Platelet Rich Plasma for the Treatment of Scarring Alopecia: A Case Series - Garg, Suruchi; Pandya, Ipsa; Bhatt, Sonali (Archives of Clinical and Medical Case Reports, 2019)
Objective: To study the effect of addition of platelet rich plasma (PRP) to the hair transplantation for scarring alopecia. Methods: An evaluation of the patients with detailed history, clinical examination and laboratory investigations was done. Routine baseline investigations and skin biopsy were done in order to rule out any activity of the underlying disease process. Freshly prepared Platelet rich plasma (PRP) using YCELL BIO kit was injected in freshly done slits over recipient area. Results: A total of 4 cases were studied- A 26 years old male with cleft lip surgical scar with absent hair growth on the middle third of the upper lip, a 22 year old male with a 5 year old post traumatic depressed scar over the junction of medial and lateral third of the right eyebrow, a 17 year old boy with a post burn scar over his left upper lip and adjoining lower cheek area and a 55 years old post menopausal female, an already diagnosed and treated case of frontal fibrosing alopecia (FFA). Hair transplantation was performed with follicular unit extraction (FUE). Freshly prepared PRP was injected intradermally after creating the slits. In all the cases, there was a good survival rate of the healthy hair follicles, accompanied by improvement in the texture of the surrounding skin. Conclusions: Platelet rich plasma, being a cocktail of growth factors, can bring vitality to the tissue and improve its vascularity, thus making it more receptive to the transplant. Additionally, with the improved vascularity of the recipient bed and activated fibroblasts, there is accelerated hair growth and better cosmetic outcomes of the scar.